Integrative taxonomy reveals the presence of a new species of Cyanea (Scyphozoa: Discomedusae: Semaeostomeae: Cyaneidae) from the West coast of Africa - Samsodien, Yusra; Brown, Michael K; Gibbons, Mark J (Zootaxa, 2024)
A new species of Cyanea is described from trawl samples collected in the Gulf of Guinea during 2017 and 2019. The species is a member of the nozakii-group, possessing interrupted radial septa, and is characterised by, inter alia, deeper rhopalial than velar marginal clefts, a uniformly papillose exumbrella, up to 200 tentacles per tentacle cluster and a dense network of anastomosing canals in broadly quadratic lappets. The species can be distinguished genetically from its congeners at both ITS1 and COI (minimum of 14.4% intergroup variation) regions as confirmed by multiple phylogenies and K2P analyses. This is the first record of a nozakii-group member in the Atlantic Ocean and the first description of the genus Cyanea from the west coast of Africa and the tropical Atlantic Ocean.